(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2024)
The adoption of Open and Distance Learning (ODL) has gained considerable attraction as a transformative educational approach, offering unparalleled flexibility and accessibility to learners while accommodating a multitude of diverse commitments. In the context of Nepal, ODL presents itself as a powerful method to mitigate the persistent challenges of educational access and exclusivity. This research underscores to focus into the intricacies of motivation that drive students to enroll in ODL programs within the hallowed precincts of the Faculty of Education (FOE) at Tribhuvan University (TU). This study carefully examines the factors influencing students’ motivation to choose ODL programs, providing insights for improving program design and support. The study applied a quantitative approach, collecting data through a structured Google Forms questionnaire and analyzing results using statistical tools. The study revealed key motivations for ODL enrollment, including a strong preference for independent online learning and recognition of ODL’s career and academic benefits. However, the results highlight lower perceptions of interaction within ODL classes. Findings further show that gender and caste/ ethnicity significantly affect motivation, reflecting disparities in access. On the other hand, demographics like provinces, religion, study programs, device used, employment status, and training involvement have limited impact on motivation. The results hold substantial significance in the discourse on ODL in Nepal’s education landscape. This research calls upon educational institutions to address interaction concerns and adapt strategies to diverse demographic motivations for effective ODL program delivery.